Increasing sleep duration to lower beat‐to‐beat blood pressure: a pilot study. (22nd November 2012) - Haack, Monika; Serrador, Jorge; Cohen, Daniel; Simpson, Norah; Meier‐Ewert, Hans; Mullington, Janet M.
Summary: Strong evidence has accumulated over the last several years, showing that low sleep quantity and/or quality plays an important role in the elevation of blood pressure. We hypothesized that increasing sleep duration serves as an effective behavioral strategy to reduce blood pressure in prehypertension or type 1 hypertension. Twenty‐two participants with prehypertension or stage 1 hypertension, and habitual sleep durations of 7 h or less, participated in a 6‐week intervention study. Subjects were randomized to a sleep extension group (48 ± 12 years, N  = 13) aiming to increase bedtime by 1 h daily over a 6‐week intervention period, or to a sleep maintenance group (47 ± 12 years, N  = 9) aiming to maintain habitual bedtimes. Both groups received sleep hygiene instructions. Beat‐to‐beat blood pressure was monitored over 24 h, and 24‐h urine and a fasting blood sample were collected pre‐ and post‐intervention. Subjects in the sleep extension group increased their actigraphy‐assessed daily sleep duration by 35 ± 9 min, while subjects in the sleep maintenance condition increased slightly by 4 ± 9 min ( P  = 0.03 for group effect). Systolic and diastolic beat‐to‐beat blood pressure averaged across the 24‐h recording period significantly decreased from pre‐ to post‐intervention visit in the sleep extension group by 14 ± 3 and 8 ± 3 mmHg, respectively ( P  < 0.05). Though the reduction of 7 ± 5 and 3 ± 4 mmHg in the sleep maintenance group was not significant, it did not differ from the blood pressure reduction in the sleep extension group ( P  = 0.15 for interaction effect). These changes were not paralleled by pre‐ to post‐intervention changes in inflammatory or sympatho‐adrenal markers, nor by changes in caloric intake. While these preliminary findings have to be interpreted with caution due to the small sample size, they encourage future investigations to test whether behavioral interventions designed to increase sleep duration serve as an effective strategy in the treatment of hypertension.